Pedagogical potential of mini-handball in optimising the psychophysiological state of primary school pupils during physical culture lessons - Sidorov, N.V.; Ivanenkov, A.S. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to assess the pedagogical effectiveness of incorporating mini-handball elements into physical culture lessons for optimising the psychophysiological state of primary school pupils. Methods and structure of the study. The study involved pupils aged 8–11, divided into two groups: an experimental group (following a programme enriched with mini-handball elements) and a control group (following the standard curriculum). Diagnostic tools included pedagogical testing of physical qualities (speed, coordination, strength, endurance, flexibility). Data processing was performed using the non-parametric Rosenbaum Q-test and the parametric Student’s t-test for independent samples. Results and conclusions. Statistical analysis revealed significant positive changes in the experimental group compared with the control group across several key indicators: speed, coordination, and strength abilities. By the end of the pedagogical experiment, the experimental group demonstrated statistically significant improvement in six of eight assessed parameters (p<0.05). The results indicate a high pedagogical effectiveness of mini-handball as a game-based technology in physical culture lessons. Its inclusion in the educational process promotes not only the development of physical qualities but also the optimisation of the functional state of primary school pupils’ bodies, which is an important condition for enhancing their cognitive activity and academic performance.